Adaptation and relative stability of bread wheat cultivars in subregion V South (l) (Semiárida, 2020)
Stability and relative adaptation of bread wheat cultivars were analyzed through years at the EERA INTA Anguil (LP) using the methodology proposed by Finlay and Wilkinson (1963) they make a regression between individual s yields and environmental indexes. The regression coefficients so obtained are a value of the relative adaptation and their statistic differences have been tested against average adaptation (b=1). The determination coefficient r2 was used to evaluate relative stability and its significance was proved against the most stable cultivar r2 (Bilbro and Ray, 1976). The analysis of variance let us know differences between cultivars and current cultivar-environment interaction for yields and test weight (Kg per hectoliter). Late in maturity cultivars definitively inscripted showed differences among yields and they interacted lightly with environment while uniformity t o r test weight was found, Bordenave Puán and Buck Naposta overcame the average yield. In the other hand, late in maturity cultivars provisionally inscripted resulted homogeneous in yields and did not inter act with environment, keeping an equal or even greated stability than those mentioned above, with adaptation to specific environments. Test Weight did hot interact with environment but their values were significantly different; Early maturity cultivars provisionally inscripted yields overcame those of definitively inscripted cultivars (1771 kg/ha vs. 1649 kg/ha) while adaptation stability resulted similar. A light interaction with environment was observed in both groups. La Paz INTA had the Lowest; yield and test weight among Its group and the same happened with Ñandu INTA a Leones INTA definitively inscripted although not as markedly as the two mentioned above. There were neither test weight differences nor environment interaction with this character.